Flights-to-and-from-Quality with Islamic and Conventional Bonds in the COVID-19 Pandemic Era: ICEEMDAN-Based Transfer Entropy - Ahmed Bossman; Samuel Kwaku Agyei; Peterson Owusu Junior; Ellen Animah Agyei; Patrick Kwashie Akorsu; Edward Marfo-Yiadom; George Amfo-Antiri (Complexity)
We revisit the flight-to-quality (FTQ) and flight-from-quality (FFQ) occurrences vis-à-vis the stock-bond nexus across differing investment time scales in the COVID-19 era, using a novel technique hinged on a denoised frequency-domain transfer entropy. Our findings divulge that flights, both FTQ and FFQ, could be attained during stress periods. Generally, in the intermediate term of the COVID-19 pandemic, both Islamic and conventional bonds could act as safe havens, diversifiers, and hedges for international equities, and the same could be observed for international equities. We reiterate empirically that flights may improve the financial system’s stability and robustness by allowing diversity to be effective when it is most required. The findings have financial and portfolio implications for investors considering how to deploy their investments in the COVID-19 era. Our findings may impact policymakers’ responses to changes in various asset classes, allowing them to better monitor financial markets and adjust macroeconomic policies.